OPTIMALISASI WAKTU TUNGGU RAWAT JALAN DENGAN METODE LEAN HEALTHCARE DI KLINIK PRATAMA - Novita Nuraini; Rossalina Adi Wijayanti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
The length of outpatients’ service waiting time reflects how health care facilities manage the service components adjusted to the patient's situation and expectations. Pratama Clinic dr. M. Suherman is a clinic that provides first-rate outpatients services where there are problems found on waiting times that are not yet standardized as stated in Kepmenkes No. 129, 2008 about the minimum service standard that it should be in 60 minutes. Thus, this research intends to make the outpatients waiting time in this clinic be more efficient by sticking to the standard of outpatients care. It implements lean healthcare as the research method with root withdrawal using fishbone and 5M management elements. It is a qualitative research and the data are collected by employing interview, observation, and brainstorming techniques. This research reveals the following results; the outpatients’ service waiting time in Pratama Clinic dr. M. Suherman averaged 108 minutes with a ratio of percentage between Value Added and Non Value Added is 20.83%: 79.16%, therefore, it means that the service process to the outpatients is not yet efficient. The unit that sends the most waste comes from general polyclinic. It is caused by several factors such as the speed of the number of outpatients registering in general polyclinic runs over the speed of the polyclinic service and the time of the outpatients' examination at each doctor range too long.